2018
DOI: 10.4103/jlp.jlp_81_18
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular hydrolytic enzyme activities of the different Candida spp. isolated from the blood of the Intensive Care Unit-admitted patients

Abstract: BACKGROUND: Candida spp. secretes various extracellular hydrolytic enzymes. These enzymes are the important virulence factor for the pathogenesis of Candida. We assessed four different enzymatic activities of Candida isolates obtained from bloodstream infections. MATERIALS AND METHODS: We isolated 79 strains of different Candida species from the blood of the Intensive Care Unit-admitted patients. Species were identified by conventional methods including culture characteristic, germ tube, sugar assimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 19 publications
4
32
2
1
Order By: Relevance
“…The proteolytic action of this enzyme also attributed the tissue invasion and penetration. 40 In the present study, it was found that ScAgNPs at 500 µg/mLinhibits production of SAPs by 82.0, 72.0, 77.5, 67.0, and 83.7% in C. albicans, C. tropicalis, C. dubliniensis, C. parapsilosis, and C. krusei, respectively (Figure 7). Similar results were previously reported by Hamid et al, 23 who found that AgNPs synthesized by fungi Aspergillus spp inhibit the secretion of A B SAPs in albicans and non-albicans isolates of Candida.…”
Section: Antimicrobial Activity Of Scagnpsmentioning
confidence: 50%
“…The proteolytic action of this enzyme also attributed the tissue invasion and penetration. 40 In the present study, it was found that ScAgNPs at 500 µg/mLinhibits production of SAPs by 82.0, 72.0, 77.5, 67.0, and 83.7% in C. albicans, C. tropicalis, C. dubliniensis, C. parapsilosis, and C. krusei, respectively (Figure 7). Similar results were previously reported by Hamid et al, 23 who found that AgNPs synthesized by fungi Aspergillus spp inhibit the secretion of A B SAPs in albicans and non-albicans isolates of Candida.…”
Section: Antimicrobial Activity Of Scagnpsmentioning
confidence: 50%
“…60 However, other studies have shown that this enzyme activity is found in C. krusei. [61][62][63] Whether this discrepancy is due to different methodologies used to measure phospholipase activity or reflects the phenotypical plasticity of the species remains to be addressed. Nonetheless, the C. krusei genome contains two putative orthologs of the PLB gene family that encodes for the major C. albicans secreted phospholipase activity (Table 1).…”
Section: Recent Understanding Of the Host-pathogen Interaction Virulementioning
confidence: 99%
“…In C. albicans , secreted hydrolytic enzymes are considered to be important destructive factors that damage host tissues, providing nutrients for its propagation. However, the production of these hydrolytic enzymes is very low or even null in C. glabrata, wherefore its importance for virulence does not seem to be as relevant as it is in C. albicans [67,68,69,70,71,72,73]. The proteinase enzyme is responsible for protein degradation resulting in tissue invasion.…”
Section: Host Damage and Invasionmentioning
confidence: 99%
“…Otherwise, phospholipases promote the destruction of cell membrane phospholipids, causing cell damage and lysis which allows a greater invasive capacity [76]. Some of the C. glabrata strains are able to produce these enzymes [67,68,70,71,77], which appear to play a role in C. glabrata -associated persistent candidemia [9]. However, phospholipase production in C. glabrata is lower than in C. albicans, and in some cases inexistent [69,72,73], therefore its relation to C. glabrata virulence is not clear and needs further analysis.…”
Section: Host Damage and Invasionmentioning
confidence: 99%